Secreted Protein Acidic and Rich in Cysteine Mediates the Development and Progression of Diabetic Retinopathy - Luo, Liying; Sun, Xi; Tang, Min; Wu, Jiahui; Qian, Tianwei; Chen, Shimei; Guan, Zhiyuan; Jiang, Yanyun; Fu, Yang; Zheng, Zhi (Frontiers in Endocrinology, 2022)
Backgrounds Diabetic retinopathy (DR) is one of the most severe microvascular complications of diabetes mellitus (DM). SPARC has been discovered to play an important role in many diseases but in DR, in which the effects and mechanisms are poorly understood. Methods The patients’ serum and vitreous SPARC levels were tested by ELISA analysis and then the Gene Expression Omnibus (GEO) dataset also been used to understand the key role of the target gene in DR. In high glucose-induced and ablation SPARC and integrin β1 of human retinal capillary endothelial cells (HRCECs), we analyzed the mRNA and protein level by RT-PCR, Immunohistochemical and Western blotting. The cell apoptosis, cell viability, and angiogenesis were analyzed by flow cytometry, CCK-8, and tube formation. Results The result revealed that DR patients have a high level of SPARC level in serum and vitreous. Interference of SPARC could decrease the expressions of inflammatory factors, VEGFR, suppress apoptosis and angiogenesis, increase cell viability in the retinal tissue of DR by regulating integrin β1 and inhibiting (High Glucose) HG-induced apoptosis of HRCECs. Conclusion SPARC promotes diabetic retinopathy via the regulation of integrin β1. The results of this study can provide an important reference for the development of drugs for the treatment of DR.